Pathogen blockade of TAK1 triggers caspase-8-dependent cleavage of gasdermin D and cell death - Orning, Pontus; Weng, Dan; Starheim, Kristian; Ratner, Dmitry; Best, Zachary; Lee, Bettina; Brooks, Alexandria; Xia, Shiyu; Wu, Hao; Kelliher, Michelle A; Berger, Scott B; Gough, Peter J; et al. (Science (American Association for the Advancement of Science), 2018)
Limited proteolysis of gasdermin D (GSDMD) generates an N-terminal pore-forming fragment that controls pyroptosis in macrophages. GSDMD is processed via inflammasome-activated caspase-1 or -11. It is currently unknown whether macrophage GSDMD can be processed by other mechanisms. Here, we describe an additional pathway controlling GSDMD processing. The inhibition of TAK1 or IκB kinase (IKK) by the effector protein YopJ elicits RIPK1- and caspase-8-dependent cleavage of GSDMD, which subsequently results in cell death. GSDMD processing also contributes to the NLRP3 inflammasome-dependent release of interleukin-1β (IL-1β). Thus, caspase-8 acts as a regulator of GSDMD-driven cell death. Furthermore, this study establishes the importance of TAK1 and IKK activity in the control of GSDMD cleavage and cytotoxicity.